“DIGITAL TRANSFORMATION AS A FACTOR OF CHANGE IN ECUADOR'S PRODUCTIVE MATRIX” - Nazareno, Master Dania Onora de León (IJRDO - Journal of Social Science and Humanities Research, 2023)
In the current context, digital transformation has become a fundamental factor for the change of the productive matrix in Ecuador. This is because the world is becoming increasingly digital and companies need to adapt to this new reality to remain competitive in the domestic and international market. However, despite the efforts of the Ecuadorian government to promote digital transformation, there are still obstacles that limit its implementation in an efficient and effective way: insufficient knowledge on the subject and its benefits for social practice. Many companies have not yet adopted digital technologies in their processes and activities. On the other hand, there are barriers such as lack of internet access in some rural areas and lack of training and education in digital skills. The objective of this study is to provide an analysis of the levels of intersectional interdependence in the context of Ecuador's productive matrix, identifying the main challenges, strengths and opportunities, so that it allows proposing recommendations for their effective integration with the digital transformation. The research methodology consisted of reviewing the existing literature on digital transformation and its integration into Ecuador's productive matrix. Information was also gathered from studies and statistical data related to the level of adoption of digital technologies in the country. The findings revealed that, although digital transformation has advanced in some sectors of the Ecuadorian economy, there is still great potential for growth in others. In addition, it was identified that the main barriers to the implementation of digital transformation are the lack of investment in technology, the lack of training and education in digital skills and the lack of awareness of the benefits of digital transformation. As a central conclusion, it can be stated that digital transformation is a key factor for the change of the productive matrix in Ecuador. However, it is necessary to overcome the barriers and challenges that exist in the implementation process. To this end, policies and programs must be established to encourage the adoption of digital technologies, communication infrastructures must be improved, and education and training in digital skills must be encouraged. This is the only way to achieve a real change in the country's productive matrix and take full advantage of the opportunities offered by the digital era.